Mildred Wells using Hart moisture meter at Hercules Hopewell plant - Hercules Incorporated (1961)
General view of employee Mildred Wells using a Hart moisture meter to measure the moisture in a sample of carboxymethyl cellulose (CMC) at the Hercules Powder Company plant in Hopewell, Virginia. Also known as cellulose gum or tylose powder, CMC is a cellulose derivative commonly used as a thickening agent or to stabilize emulsions in a range of materials, including toothpaste, water-based paints, detergents, and various paper products. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Scientific apparatus and instruments; Research, Industrial; Hercules Incorporated; Corporations; Cellulose; Women employees; Wells, Mildred